1975
DOI: 10.1093/neurosurgery/22.cn_suppl_1.573
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Spinal Cord Blood Flow

Abstract: The response of SCBF to changes in pACO2 was tested in Rhesus monkeys under normotensive conditions. A sigmoid shaped response was demonstrated. At a pACO2 of 10 to 50 mm. Hg, SCBF remained constant and in the normal range. As the pACO2 was raised from 50 to 90 mm. Hg, SCBF increased. Further increases in the pACO2 above 90 mm. Hg failed to effect further changes in SCBF. We conclude from these data that SCBF is somewhat less responsive than CBF to changes in pACO2. Next, the effect of changes in MAP on SCBF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 0 publications
0
23
1
1
Order By: Relevance
“…They reported flow rates for dorsal horn grey matter electrodes which would be more appropriate for white matter (17 cc/100 grams/minute). 12 Due to indicator diffusion between grey and white matter, this measured flow was most likely a weighted mean for the whole dorsolateral quandrant of the spinal cord. This is similar to our inability to demonstrate appropriate grey matter clearance rates (70 to 90 cc/100 grams/minute) in rabbit cortex.…”
Section: Relevant Observations By Othersmentioning
confidence: 99%
“…They reported flow rates for dorsal horn grey matter electrodes which would be more appropriate for white matter (17 cc/100 grams/minute). 12 Due to indicator diffusion between grey and white matter, this measured flow was most likely a weighted mean for the whole dorsolateral quandrant of the spinal cord. This is similar to our inability to demonstrate appropriate grey matter clearance rates (70 to 90 cc/100 grams/minute) in rabbit cortex.…”
Section: Relevant Observations By Othersmentioning
confidence: 99%
“…Further increases above 90 mm Hg had no effect on SCBF, which had reached a physical maximum. 45 In another study, Kobrine and coworkers 47 found that SCBF remained constant when MABP was between 50 and 135 mm Hg. Below 50 mm Hg, vascular resistance decreased maximally, and SCBF became a function of MABP.…”
mentioning
confidence: 94%
“…When MABP fell below 40 mm Hg, SCBF dropped significantly. 38 Kobrine and associates 45 found that when CO 2 pressure was between 10 to 50 mm Hg in monkeys, SCBF stayed constant. When the pressure of CO 2 surpassed 50 mm Hg, SCBF increased.…”
mentioning
confidence: 94%
“…Раніше межі авторегуляції СМ визначались як САТ від 50-60 до 120-135 мм рт.ст. [24,28]. Протягом останніх років Drummond та його колеги поставили під сумнів прийняте попередньо судження щодо діапазону 50 мм рт.ст., що стано-вить відповідну та сумісну нижню межу авторегу-ляції головного мозку в людини.…”
Section: контроль артеріального тиску при проведенні нейроаксіальноїunclassified